The Heart-Team Approach for the Treatment of Radiation-Induced Aortic Stenosis and Coronary Artery Disease: A Case ReportNovel Teaching Points - Eve Belzile-Dugas, MD (Elsevier, 2021)
We describe the case of a 54-year-old woman admitted to the cardiology ward for the correction of radiation-induced aortic stenosis and coronary artery disease. After careful workup, she underwent surgical aortic valve replacement and aortocoronary bypass with venous grafts. This case demonstrates the late cardiovascular complications that can develop after radiation therapy for cancer, and the surgical complexity of these patients. Thorough workup is needed for the treatment of radiation-induced valvulopathy and coronary artery disease, as these patients are often poor surgical candidates with hostile chests. Multidisciplinary heart-team assessment is paramount, and consideration should be given to catheter-based approaches. RÉsumÉ: Nous décrivons le cas d’une femme de 54 ans admise en cardiologie pour la correction d’une sténose aortique radio-induite et une coronaropathie. Après un bilan minutieux, elle a subi un remplacement valvulaire aortique chirurgical et un pontage aortocoronarien à l’aide de greffons veineux. Ce cas démontre les complications cardiovasculaires tardives qui peuvent survenir après la radiothérapie administrée pour un cancer, et la complexité de l’intervention chirurgicale de ces patients. Un bilan complet est nécessaire avant le traitement de la valvulopathie radio-induite et de la coronaropathie, puisque ces patients sont souvent de mauvais candidats à l’intervention chirurgicale en raison de thorax « hostiles ». Il est primordial que l’équipe multidisciplinaire en cardiologie réalise l’évaluation et il faudrait envisager les approches par cathéter.